The Effect of Religious Understanding, Social Welfare, and Cultural Values of The Community Towards The Sacred Tomb - Firdaus, Yusuf Rohadian; Nurhayati, Sri; Noor, Agus Hasbi (Jurnal Ilmiah Profesi Pendidikan, 2024)
This research aims to determine the effect of religious understanding, social welfare and community cultural values on the sacredness of Astana Dua in Kampung Pasir Kaur, Weninggalih Village, Sindangkerta District, West Bandung Regency. The research method uses a quantitative approach with inferential statistical analysis. The research results prove that each independent variable (x1, x2 and x3) either partially or jointly has an influence on the dependent variable (Y). Strictly speaking, this study can accept and prove the hypothesis which states that, together the variables X1, X2 and X3 have a very strong influence on the Astana Dua Sacrality with a correlation coefficient of 0.941 and the significance of the ANOVA test (F test) is at a value of 0.000. The coefficient of determination together is 88.50%, and the remaining 11.50% is the influence of factors other than religious understanding, social welfare and cultural values that require further research. the implications for community education in Kampung Pasir Kaur are profound. Educational initiatives must be thoughtfully designed to balance religious, economic, and cultural learning, promoting a well-rounded understanding that respects and upholds the community’s traditional values and sacred sites. This integrated approach can serve as a model for other communities facing similar challenges, providing a blueprint for education that supports cultural preservation while fostering socioeconomic and spiritual growth.